Bioinspired composite structures: A comprehensive review of natural materials, fabrication methods, and engineering applications - M A Shadab Siddiqui; M S Rabbi; Radif Uddin Ahmed; Fahad Alam; M A M Hossain; Shamim Ahsan; Nur Mohammad Miah (Composites Part C: Open Access)
Biomimetic materials have emerged as a promising alternative to synthetic materials due to their potential to mimic biological architecture across multiple scales, from nanofibrous architectures to macroscopic gradients. Natural materials, such as bone, wood, spider silk, and mollusk shells, have remarkable mechanical properties owing to their complex hierarchical structure. They process a unique combination of organic and inorganic components. Inspired by these biological composites, advanced synthetic materials with improved strength, toughness, and functionality have been developed. This review highlights the multifaceted approaches to creating scaffolds that mimic extracellular matrix (ECM) and tissue hierarchies across multiple length scales. Among these, nacre, mollusk shells, and eggshells exhibit remarkable versatility in their adaptation to various fabrication methods, suggesting their promising role in future biomimicry. Also, various fabrication techniques for biomimetic composite scaffolds are explored, including 3D printing, electrospinning, and self-assembly methods. The strong focus on biomedical applications highlights the natural synergy between bioinspired materials and medical innovations, particularly in tissue engineering and regenerative medicine. This overview of current strategies and future directions in the field will be of interest to researchers in materials science, tissue engineering, as well as biomedicine. The paper presents the possibility of biomimetic composites changing the way many applications, from biomedical implants to sustainable engineering solutions.